A New Net to Go Fishing: Messages From International Evidence-Based Research and Kaupapa Māori Research - Manning, Richard F.; Macfarlane, Angus H.; Skerrett, Mere; Cooper, Garrick; De Oliveira (Andreotti), Vanessa; Emery, Tepora (The Australian Journal of Indigenous Education, 2011)
This article draws upon a Māori metaphor to describe the theoretical framework underpinning the methodology and findings of a research project completed by researchers from the University of Canterbury, New Zealand, in 2010. It explains how and why the project required the research team to synthesise key information from four New Zealand Ministry of Education Best Evidence Synthesis (BES) reports as well as kaupapaMāori research associated with the Ministry's Ka HikitiaMāori Education Strategy. The key messages outlined in this article were designed by the research team to serve as a new tool to assist whānau (family) and iwi (tribe) to actively engage in the New Zealand schooling system and assert their rights in accordance with the principles of the Treaty of Waitangi (1840). Given the large number of Māori children attending Australian schools, the findings of this research may be of interest to Australian educationalists.